Elf5 is essential for early embryogenesis and mammary gland development during pregnancy and lactation - Zhou, Jiong (2005)
Elf5 is an epithelial-specific ETS factor. Embryos with a null mutation in the Elf5 gene died before embryonic day 7.5, indicating that Elf5 is essential during mouse embryogenesis. Elf5 is also required for proliferation and differentiation of mouse mammary alveolar epithelial cells during pregnancy and lactation. The loss of one functional allele led to complete developmental arrest of the mammary gland in pregnant Elf5 heterozygous mice. A quantitative mRNA expression study and Western blot analysis revealed that decreased expression of Elf5 correlated with the downregulation of milk proteins in Elf5(+/−) mammary glands. Mammary gland transplants into Rag(−/−) mice demonstrated that Elf5(+/−) mammary alveolar buds failed to develop in an Elf5(+/+) mammary fat pad during pregnancy, demonstrating an epithelial cell autonomous defect. Elf5 expression was reduced in Prolactin receptor (Prlr) heterozygous mammary glands, which phenocopy Elf5(+/−) glands, suggesting that Elf5 and Prlr are in the same pathway. Our data demonstrate that Elf5 is essential for developmental processes in the embryo and in the mammary gland during pregnancy.